2013
DOI: 10.1027/1614-2241/a000057
|View full text |Cite
|
Sign up to set email alerts
|

Skewness and Kurtosis in Real Data Samples

Abstract: Parametric statistics are based on the assumption of normality. Recent findings suggest that Type I error and power can be adversely affected when data are non-normal. This paper aims to assess the distributional shape of real data by examining the values of the third and fourth central moments as a measurement of skewness and kurtosis in small samples. The analysis concerned 693 distributions with a sample size ranging from 10 to 30. Measures of cognitive ability and of other psychological variables were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
184
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 349 publications
(228 citation statements)
references
References 72 publications
9
184
0
1
Order By: Relevance
“…The other two distributions analyzed had a fixed skewness, γ 1 = 0.8, and two values of kurtosis, γ 2 = 2.4 and γ 2 = 5.4. These values are well within the ranges of skewness and kurtosis that are observed in real-world settings (Blanca et al, 2013;Lei & Lomax, 2005), and they are also the values used in the study by Arnau et al (2012).…”
Section: Study Variablessupporting
confidence: 72%
See 2 more Smart Citations
“…The other two distributions analyzed had a fixed skewness, γ 1 = 0.8, and two values of kurtosis, γ 2 = 2.4 and γ 2 = 5.4. These values are well within the ranges of skewness and kurtosis that are observed in real-world settings (Blanca et al, 2013;Lei & Lomax, 2005), and they are also the values used in the study by Arnau et al (2012).…”
Section: Study Variablessupporting
confidence: 72%
“…Among the strongly biased distributions, a number of simulation studies have analyzed the log-normal distribution Keselman, Kowalchuk, & Boik, 2000;and Kowalchuk et al, 2004, among others). The distributions used in the present study had positive values of skewness and kurtosis, given that such values are used in simulation studies and are also the most common found in distributions of psychological variables (Blanca et al, 2013). Regarding the degree of contamination, the extreme values chosen were γ 1 = 1.75 and γ 2 = 5.9, which correspond to the log-normal distribution, one of the most widely studied.…”
Section: Study Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…ANOVA) require that the assumption of normality be fulfilled, in other words, the dependent variable must be distributed according to the normal curve. However, the variables encountered in the field of health and social sciences often do not follow a normal distribution (Blanca, Arnau, Bono, López-Montiel & Bendayan, 2013;Limpert, Stahel & Abbt, 2001;Micceri, 1989). Examples of such variables in the health sciences are survival times for certain types of cancer (Claret et al, 2009;Qazi, DuMez & Uckun, 2007) or the age at onset of Alzheimer's disease (Horner, 1987), while in the social sciences it is the case of variables such as social support (Matud, Carballeira, Lopez, Marrero & Ibáñez, 2002), physical and verbal aggression in couple relationships (Soler, Vinyak & Quadagno, 2000), certain psychosocial aspects of addictions (Deluchi & Bostrom, 2004), post-traumatic stress (Sullivan & Holt, 2008), reaction times or response latency (ShangWen & Ming-Hua, 2010;Ulrich & Miller, 1993; Van der Linden, 2006), certain attentional skills (Brown, Weatherholt & Burns, 2010) and variables of a psychophysiological nature (Keselman, Wilcox & Lix, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The criteria used to evaluate this include how long the process takes (Afflerbach, 1990), its replicability (Ripley, 1990) and the degree to which the generated distribution fits the theoretical model (Bang, Shumacker & Schlieve, 1998), with this latter criterion being of particular interest for determining the accuracy of the procedure. In this context, it is especially important to evaluate the suitability of data generators for generating non-normal distributions, both known and unknown (Demirtas, 2007), as these types of distributions are commonly encountered in real data (Blanca et al, 2013;Limpert et al, 2001;Micceri, 1989).…”
Section: Introductionmentioning
confidence: 99%